2021
DOI: 10.1177/03635465211039834
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcome Scores and Rate of Return to Sport After Hip Arthroscopic Surgery: A Sex-Based Comparison in Professional and Collegiate Athletes

Abstract: Background: No studies have compared outcomes and return to sport (RTS) after hip arthroscopic surgery between matched groups of male and female athletes with a minimum 2-year follow-up. Purpose: (1) To report minimum 2-year postoperative patient-reported outcome (PRO) scores and the RTS rate for elite female athletes undergoing hip arthroscopic surgery for femoroacetabular impingement (FAI) and (2) to compare clinical results with a matched control group of elite male athletes. Study Design: Cohort study; Lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 46 publications
2
17
1
1
Order By: Relevance
“…Shibata et al 55 performed a nonmatched comparison of elite-level male and female athletes and demonstrated excellent RTS rates in both male and female athletes. Similarly, Glein et al 21 also demonstrated favorable outcomes at a minimum 2-year follow-up in a cohort of elite female athletes undergoing primary hip arthroscopy; however, in their study, female athletes demonstrated statistically significantly greater improvement in PROs compared with male patients. The outcomes in the present study provide further evidence to support similar outcomes in male and female athletes undergoing hip arthroscopy with labral reconstruction despite the preoperative differences present in bony morphology.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Shibata et al 55 performed a nonmatched comparison of elite-level male and female athletes and demonstrated excellent RTS rates in both male and female athletes. Similarly, Glein et al 21 also demonstrated favorable outcomes at a minimum 2-year follow-up in a cohort of elite female athletes undergoing primary hip arthroscopy; however, in their study, female athletes demonstrated statistically significantly greater improvement in PROs compared with male patients. The outcomes in the present study provide further evidence to support similar outcomes in male and female athletes undergoing hip arthroscopy with labral reconstruction despite the preoperative differences present in bony morphology.…”
Section: Discussionmentioning
confidence: 83%
“…Recent studies have established favorable outcomes in athletes undergoing labral reconstruction, but no studies have evaluated sex-based differences in presentation and outcomes of these athletes. 21 , 28 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hip arthroscopy is being performed increasingly frequently in athletes and has shown favorable outcomes and high rates of return to sports (RTS). 7,14,27,33,34 Labral function restoration and adequate treatment of femoroacetabular impingement syndrome (FAIS) are critical components of successful outcomes after primary hip arthroscopy. 3,57,59 In cases of irreparable labral tears, labral reconstruction has shown promising short–term outcomes and RTS in athletes in the primary setting.…”
mentioning
confidence: 99%
“…38,46,63 Although recent studies have established favorable outcomes in athletes at midterm follow-up, to our best knowledge, there are no studies that have evaluated sex-based differences in the presentation and outcomes of these athletes. 25,33,43,57,58 The purpose of this study was (1) to report minimum 5year patient-reported outcome (PRO) scores as well as RTS and continuation of sport (CTS) rates for elite female athletes undergoing hip arthroscopic surgery for FAIS and (2) to compare clinical results with those of a matched control group of elite male athletes. It was hypothesized that elite female athletes would achieve favorable outcomes at midterm follow-up and that these outcomes would be similar to those of a control group of elite male athletes.…”
mentioning
confidence: 99%